EFFECTIVE USE OF THE EXPERIENCE OF ADVANCED FOREIGN COUNTRIES IN STATE SUPPORT OF TOURISM - Jabborova Zukhra , Abdigani kizi (THE INNOVATION ECONOMY, 2025)
This article examines the importance of the tourism sector in the socio-economic development of the country, increasing the competitiveness of various industries in the region, and, in turn, the growth of the socio economic development of the region and its development based on certain factors. The article provides suggestions and recommendations on the development of innovative activities in the field of tourism services and the improvement of economic mechanisms for state support of innovative activities, as well as innovative technologies, their content, application and effectiveness.